Evidence Based Update on Psychosocial Treatments for Eating Disorders in Children and Adolescents - Datta, Nandini; Matheson, Brittany E.; Citron, Kyra; Van Wye, Eliza Margaret; Lock, James D. (Journal of clinical child and adolescent psychology, 2023)
Eating disorders (EDs) are life-threatening psychiatric illnesses that occur in adolescents. Unfortunately, limited randomized controlled trials exist to address EDs in this vulnerable population. The current review updates a prior Journal of Clinical Child and Adolescent Psychology review from 2015. The recommendations in this review build upon those that were previously published. This update was completed through a systematic search of three major scientific databases (PsychInfo, Pubmed, and Cochrane) from 2015 to 2022 (inclusively) from three databases, employing relevant medial subject headings. Additionally, expert colleagues were asked for additional literature to include. Thirty-one new studies were added to this review. Psychosocial treatments included family therapies, individual therapy, cognitive-behavioral therapy, interpersonal psychotherapy, cognitive training, dialectical behavioral therapy, and more recently, virtual or telehealth-based practices and guided self-help modalities for carers of youth with EDs. Using the Journal of Clinical Child and Adolescent Psychology's methodological review criteria, this update found behavioral family-based treatment modalities (FBT) for both adolescent anorexia nervosa and bulimia nervosa met well-established treatment criteria. To date, there were no well-established treatments found for child and adolescent avoidant-restrictive food intake disorder, or binge eating disorder. Internet facilitated cognitive-behavioral therapy and family-based therapy were found to be possibly efficacious for binge eating disorder. Family-based treatment was found to be possibly efficacious for avoidant restrictive food intake disorder, with other clinical trials for cognitive treatment modalities under way. Ongoing research examining treatments for eating disorders in children and adolescents broadly is needed.